2018
DOI: 10.1177/0300060517737211
|View full text |Cite
|
Sign up to set email alerts
|

Are platelet volume indices related to mortality in hospitalized children on mechanical ventilation?

Abstract: ObjectivesTo investigate platelet volume indices and in-hospital mortality in children on mechanical ventilation.MethodsThis retrospective study included children aged <16 years on mechanical ventilation, and compared parameters, measured on admission, between survivors and non-survivors. Dynamic platelet volume indices over the first 7 days were visualized. Independent risk factors of mortality were identified using multivariate logistic regression analysis.ResultsOut of 2 319 children aged 28 days–3 years, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…High MPV was suggested to be associated with overall survival in various diseases such as cancer, cardiac disease, septic shock, kidney injury, and patients hospitalized in a respiratory intensive care unit (21)(22)(23)(24)(25). On the other hand, subsequent MPV and PDW are suggested to be associated with mortality in critically ill children receiving mechanical ventilation, however initial admission MPV was not associated with mortality in those children (17). There are few reports about the relationship between MPV and morbidities among large cohorts of premature newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High MPV was suggested to be associated with overall survival in various diseases such as cancer, cardiac disease, septic shock, kidney injury, and patients hospitalized in a respiratory intensive care unit (21)(22)(23)(24)(25). On the other hand, subsequent MPV and PDW are suggested to be associated with mortality in critically ill children receiving mechanical ventilation, however initial admission MPV was not associated with mortality in those children (17). There are few reports about the relationship between MPV and morbidities among large cohorts of premature newborns.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that elevated MPV at birth correlates with unfavorable outcomes for NICU patients born after <32 weeks' gestation. While precise pathophysiologic mechanisms remain elusive, platelet numbers and average size may increase in conjunction with inflammatory and thrombotic conditions (17). Young platelets are generally larger than old ones, and the presence of more young platelets indicates increased production in response to consumption, which in turn may be provoked by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Ye et al on critically ill children receiving mechanical ventilation reported that there were significant associations between PCT and PDW with mortality. These studies also demonstrated that patients with a low platelet count and high MPV and PDW survived for a shorter time than those with normal platelet indices; thus, platelet indices were proposed as a novel prognostic indicator in critically ill patients [14]. Similarly, Aydemir et al show that increase in MPV values was statistically significant for the first 3 days of sepsis [7].…”
Section: Discussionmentioning
confidence: 94%
“…So, we speculate that MPV could represent a relevant predictive marker of mortality in premature neonates with late-onset sepsis. While precise pathophysiologic mechanisms remain elusive, platelet average size may increase in conjunction with inflammation [ 26 ]. Moreover, elevated MPV may be indicative of oxidative stress in newborns [ 27 ].…”
Section: Discussionmentioning
confidence: 99%